Polyvinylidene fluoride/graphene oxide nanocomposite as anti-corrosion coating in natural gas steel pipelines - Chiong, Sie Jing (2017)
Internal corrosion causes the mechanical strength of natural gas steel pipelines to be reduced, leading to cracking. Superior properties of polyvinylidene fluoride (PVDF) makes its as an excellent candidate for the anti-corrosion coating in natural gas steel pipelines. Nevertheless, further development of PVDF nanocomposite is necessary to enhance the properties of neat PVDF in terms ofwettability, mechanical strength, anti-corrosion and impermeable property. In this research, monolayer 3aminopropyltriethoxysilane- graphene oxide (APTES-GO) with a thickness of 0.58 nm was successfully synthesized through surface functionalization of graphene oxide (GO). APTES-GO was selected as the nanofiller to be incorporated into the PVDF matrix. This is because PVDF/APTES-GO nanocomposite displayed better anticorrosion performance than GO. PVDF nanocomposites filled with various loadings of APTES-GO (0.1 to 0.5 wt%) were prepared using N,N-dimethylformamide as the solvent. The detailed anti-corrosion performance of PVDFIAPTES-GO nanocomposites coated onto carbon steel plate was evaluated using Machu, salt spray and acid immersion tests. X-ray diffraction and Fourier transform infrared spectroscopy confirmed thatthe increment ofAPTES-GO from 0.1 to 0.5 wt% loading had transformed ~- and y- to a-phase crystal. Field emission scanning electron microscopy revealed that the PVDF nanocomposite films with a thickness of 73.0 ± 3.61 urn exhibited features of the symmetric membranes. Atomic force microscopy analysis also showed that the surface roughness of PVDF nanocomposite films increased with the increase of APTES-GO loading. Besides that, PVDF nanocomposite filled with 0.4 wt% APTES-GO showed the highest water contact angle of 102° and ~306% increase in tensile modulus as compared to the neat PVDF. This nanocomposite layer (66.67 ± 4.0 urn) was found to exhibit good adhesion property with the lowest corrosion rate of 6.65 mm/yr and highest corrosion protection efficiency of 51.16% in corrosive environments.